Sub-lethal concentration of metamifop exposure impair gut health of zebrafish (Danio rerio). (September 2022) - Zhao, Feng; Guo, Mengyu; Zhang, Mengna; Duan, Manman; Zheng, Junyue; Liu, Yinchi; Qiu, Lihong
Abstract: Previous studies have demonstrated that sublethal metamifop exposures induce hepatic lipid metabolism disorder in zebrafish. Whether metamifop will cause adverse effects in zebrafish gut is unknown. In the present study, effects of metamifop on gut heath of zebrafish were investigated after sublethal concentration (0.025, 0.10 and 0.40 mg/L) exposure. Histopathology analysis showed that metamifop induced inflammation and reduction of goblet cells in the gut, indicating that gut health may be impaired. Metamifop exposure could reduce activities of digestive enzymes (lipase and alkaline phosphatase), indicating the capacity of lipid absorption were impaired. Meanwhile, the content of fatty acid-binding protein 2 (FABP2) and mRNA levels of related genes ( apoa-1a, apoe-b, fatp4, lpl and fabp2 ) were reduced in zebrafish gut after exposure to metamifop, suggesting the lipid transportation were decreased. The transcripts of genes associated with inflammation ( il-17c, tnf-α and nf-kb ) were significantly increased in 0.40 mg/L metamifop treatment group, which were 1.90-, 1.53- and 2.77-fold of the control group, respectively, confirming that metamifop induced inflammatory response in zebrafish gut. Moreover, reduction of mRNA levels of cldn-15 and elevation of lipopolysaccharides (LPS) content were observed in metamifop-treated groups, which suggested that metamifop exposure increased the intestinal permeability. Furthermore, metamifop exposure decreased the relative abundance of beneficial bacteria ( Psychrobacter and Aeromonas ) and elevated the abundance of pathogenic bacteria ( Rhodobacter and Ralstonia ) in zebrafish intestine. These results indicated that metamifop exposure at sublethal concentrations would impair zebrafish gut health, via reduction of lipids absorption, inflammatory response, elevation of permeability and microbiota disorder. Graphical abstract: Image 1 Highlights: Sublethal concentration of metamifop induced reduction of goblet cells in gut of zebrafish. Lipid absorption and transportation of zebrafish gut were impaired by metamifop exposure. Metamifop caused oxidative stress and inflammation response in zebrafish gut. Metamifop disrupted the permeability of zebrafish gut. Metamifop caused microbiota dysbiosis in zebrafish gut.